Efecto de la suplementación proteica al servicio y preparto sobre los nematodos gastrointestinales y producción lechera de cabras - Olmos, L.H. (2025)
The aim of this study was to evaluate the effect of protein supplementation at service and before delivery on the load of gastrointestinal nematodes in naturally infested dairy goats. Two groups of 17 goats were evaluated: control group (SinSu) without supplementation and supplemented (ConSu) with 19% protein during service and 45 days prepartum. The animals were monitored every 15 days during service and in the 45 days before lambing and monthly during the rest of the trial. The parasitic load (eggs per gram of feces – epg) and their differentiation into genus were determined, in addition to the hematocrit, total proteins, body condition (BCS) and clinical and Famacha grade. The weight of the offspring and milk production at 90 days were recorded. No significant differences were found in epg of the two groups before lambing, but protein supplementation resulted in a lower parasitic load in the supplemented group (p<0.03). There were no significant differences in the rest of the blood parameters, FAMACHA or BCS. Neither in the pregnancy percentage (ConSu: 94.1%; SinSu 76.4%), birth weight or total milk production at 90 days.